Correlates of Students’ Academic Resilience and Teachers’ Emotional Support - Samonte, Lyra Bell; Fermin, John Noel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the academic resilience of college students at Quirino State University-Cabarroguis Campus and its relationship with their perceived teachers’ emotional support. It was anchored on Self-Determination Theory, Social Cognitive Theory, and Positive Psychology Theory. A quantitative descriptive-correlational design was employed involving 350 first- to fourth-year tertiary students selected through stratified random sampling during School Year 2023-2024. Data were gathered using the adapted 30-item Academic Resilience Scale and Teacher’s Emotional Support Scale and analyzed using frequency, percentage, mean, standard deviation, and Pearson product-moment correlation. Findings revealed that 276 respondents, or 78.87%, were classified as having low global academic resilience, while 74 respondents, or 21.14%, demonstrated high academic resilience. Perseverance emerged as the weakest dimension, whereas reflective and adaptive help-seeking and negative affect and emotional response were rated high. Teachers’ emotional support obtained a grand mean of 3.88, interpreted as moderately true, indicating generally favorable perceptions of positive climate, teacher sensitivity, and regard for adolescent perspectives. However, individualized teacher interest received a comparatively lower rating. A weak but statistically significant positive relationship was found between academic resilience and teachers’ emotional support (r = 0.342, p < 0.001), resulting in the rejection of the null hypothesis. The study concluded that teacher empathy, encouragement, and supportive classroom environments contribute to students’ capacity to manage academic challenges, although sustained perseverance requires further development. It recommended resilience-building activities, faculty sensitivity training, mentoring, peer support, periodic student assessments, and institutional monitoring. The study supports SDG 3 on Good Health and Well-Being, SDG 4 on Quality Education, and SDG 8 on Decent Work and Economic Growth. Its sustainability impact lies in strengthening student well-being, faculty-student relationships, institutional support systems, and students’ long-term academic and professional preparedness.